Mending a broken heart by biomimetic 3D printed natural biomaterial-based cardiac patches: a review - Rosellini, Elisabetta; Cascone, Maria Grazia; Guidi, Lorenzo; Schubert, Dirk W.; Roether, Judith A.; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2023)
Myocardial infarction is a leading cause of morbidity and mortality worldwide. Cardiac tissue engineering aims to bioengineer a functional cardiac tissue, that could be used both for tissue repair, patient specific drug screening and disease modeling. To achieve this, an appropriate combination of cells, biomimetic scaffolds mimicking the structural and functional properties of the native tissue and signals is mandatory. Among scaffold fabrication techniques, three-dimensional printing, which is an additive manufacturing technique that enables to translate computer-aided designs into 3D objects, has emerged as a promising technique to develop cardiac patches with a highly defined architecture. As a further step toward the replication of complex tissues, such as cardiac tissue, more recently 3D bioprinting has emerged as a cutting-edge technology to print not only biomaterials, but also multiple cell types. Regarding bioinks, biomaterials isolated from natural sources are advantageous, as they can provide exceptional biocompatibility and bioactivity, thus promoting desired cell responses. An ideal biomimetic cardiac patch should also be enriched with additional functional properties, which can be obtained through appropriate functionalization strategies. These are essential to replicate the native tissue, such as the release of biochemical signals, immunomodulatory properties, conductivity, enhanced vascularization and shape memory effects. The aim of this review is to provide an overview of the current state of the art regarding the development of biomimetic 3D printed natural biomaterial-based cardiac patches, describing the 3D printing fabrication methods, the naturalbiomaterial based bioinks, the functionalization strategies, as well as the in vitro and in vivo applications.